'España es diferente … España cambia de piel'. Of the Festivals of Spain (1954) to the 1st International Biennial of Contemporary Music of Madrid (1964): Avant-Garde Music for the Francoist Technocracy. Issue 1 (4th March 2019) - Ferrer Cayón, Jesús
Abstract : 1964 was 'the Musical Year' of Franco's Spain, as part of the 'XXV Years of Peace'. For that reason, before analysing the I Bienal Internacional de Música Contemporánea [1st International Biennial of Contemporary Music (I IBCM)], a synoptic comment is made on the most outstanding events that previously contributed to the commemoration of that event, namely, the First Opera Festival in Madrid, the Peace Concert, the Radio and Television (RTVE) Symphony Orchestra and the 1st Festival of Music of Americas and Spain (I FMAS), since all of them represented, in the field of music, the development of Spain in the 1960s and the type of integration with Europe that the pro-Franco technocracy attempted economically. It also explains the promotion of festivals as a phenomenon of early Francoism, begun during the opening decade of the 1950s in order to combat the diplomatic isolation of Spain, promote tourism and re-educate the Spaniards.